Poor hypotheses and research waste in biology: learning from a theory crisis in psychology - Shinichi Nakagawa; David W. Armitage; Tom Froese; Yefeng Yang; Malgorzata Lagisz (BMC Biology)
Abstract While psychologists have extensively discussed the notion of a “theory crisis” arising from vague and incorrect hypotheses, there has been no debate about such a crisis in biology. However, biologists have long discussed communication failures between theoreticians and empiricists. We argue such failure is one aspect of a theory crisis because misapplied and misunderstood theories lead to poor hypotheses and research waste. We review its solutions and compare them with methodology-focused solutions proposed for replication crises. We conclude by discussing how promoting inclusion, diversity, equity, and accessibility (IDEA) in theoretical biology could contribute to ameliorating breakdowns in the theory-empirical cycle.